모바일 인스턴트 메신저에 대한 신뢰, 이모티콘 사용 태도와 이모티콘 구매의도 사이의 구조적 관계: 카카오톡 사례 - 정보희; 배정호; Jung, Bohee; Bae, Jungho (한국콘텐츠학회 논문지, 16(10), 2016)
The communication via MIM(Mobile Instant Messenger) has unique characteristics; one of them is use of emoticons. Although using emoticons in MIM is getting a lot of attention from business fields and emoticons markets in MIM is growing rapidly, there are little researches focused on emoticons in MIM in consumer behaviors and marketing area. So, the purpose of this study is to fill this theoretical and practical gap. For this purpose, we explore the effect of and trust in MIM system and attitude toward use of emoticons on purchase intention to emotions in MIM. Our study used structural equation modeling analysis; the results showed that perceived benefits and perceived risk to MIM affected trust in MIM system significantly, more specifically, while perceived benefits affected trust in MIM system positively, perceived risk affected trust in MIM system negatively. We also found that perceived usefulness of emoticon in MIM and flow experience influenced attitude toward use of emoticons positively. Lastly, trust in MIM system and attitude toward use of emoticons had positive effect on purchase intention to emoticons in MIM. The implication and limitations of this study are also discussed. 모바일 인스턴트 메신저를 통한 커뮤니케이션이 지닌 특성 중 하나인 이모티콘의 사용 비중은 최근 비약적으로 증가하며 관련 시장도 커지고 있다. 이처럼 모바일 인스턴트 메신저 내 이모티콘 시장 가치가 증대되고 있음에도 불구하고, 이에 대한 학문적 연구는 미흡한 실정이다. 본 연구는 이러한 학문적 간극(gap)을 메우고, 모바일 인스턴트 메신저 서비스 내 이모티콘 시장 확대를 위한 전략 방향을 제안하기 위해 수행되었다. 보다 구체적으로 본 연구는 국내 스마트폰 사용자들이 가장 많이 사용하고 있는 모바일 인스턴트 메신저 앱인 카카오톡을 대상으로 카카오톡 내 이모티콘 구매의도에 영향을 미치는 요인들에 대해 탐색해보고자 한다. 본 연구는 카카오톡 대학생 사용자 193명을 대상으로 설문조사를 통해 진행되었으며, 구조방정식 모형의 경로분석을 사용하여 가설 검증을 하였다. 분석 결과, 모바일 인스턴트 메신저에 대한 소비자의 지각된 혜택은 시스템 신뢰도에 양(+)의 영향을 주었고, 지각된 위험은 음(-)의 영향을 주었다. 또한 이모티콘에 대한 지각된 유용성과 플로우는 각각 이모티콘 사용태도에 양(+)의 영향을 주었다. 그리고 시스템 신뢰도와 이모티콘 사용태도는 이모티콘 구매의도에 각각 양(+)의 영향력을 주는 것으로 밝혀졌다. 본 연구는 게임이나 소셜 네트워크 서비스 등 다른 모바일 관련 서비스 컨텐츠에 비해 상대적으로 연구가 많이 진행되지 않은 모바일 인스턴트 메신저 내 이모티콘 구매에 대한 연구로서 구체적인 이론적, 실무적함의 역시 논하였다.